MEASURING THE PERFORMANCE OF REGIONAL GOVERNMENT: USING DATA ENVELOPMENT ANALYSIS (DEA) APPROACH - Zainal Putra; Muzakir Muzakir; Ishak Hasan (AFEBI Management and Business Review, 2018)
The realization of regional government expenditure in Aceh Province from 2011 – 2015 has reached the figure of Rp84.260.616.926.552,00. However, the indicator data of Aceh people’s welfare in 2016 provided information of unemployment rate in Aceh in 2015  at 9,93%. This exceeds the national unemployment rate in the same period of 6.2%. Likewise, the poverty rate of Aceh Province in 2015 was at 17.08%. While nationally, the unemployment rate was at 11.13%. This condition indicated that the regional government were still unable to prosper the people, which also means that the governments were underperformed. This was possible because of inefficient use of resources. Efficiency does not only apply to private sector but also public sector. public sector organizations are now required to be able to operate efficiently to improve the performance. Nowadays, the performance of the local government has been criticized by the public. Therefore, it is necessary to develop a performance measurement toward public organization to know the extent of performance in a certain period accurately. This study aims to determine the efficiency level of regency / city governments in Aceh Province. By using the Data Envelopment Analysis (DEA) approach, it is possible to observe which regency / city governments are performing well. This study uses input variables including regional expenditure, assets, population, civil servants and area. Output variables used include Regional Original Income (PAD), Human Development Index (HDI) and Per capita Income.The result shows that from 23 regency / city governments in Aceh Province, in the overall average from 2011 - 2015, there were only 5 regency / city governments (21.74%) who were efficient in running their government (efficiency score 1.00) , namely Banda Aceh, Langsa, Lhokseumawe, Sabang and Subulussalam. Therefore, the regency / city government has a good performance.Keywords: Performance and DEA, Regency / city governments